Web-Based Acceptance and Commitment Therapy for Depressive Symptoms With Minimal Support: A Randomized Controlled Trial. (November 2015) - Lappalainen, Päivi; Langrial, Sitwat; Oinas-Kukkonen, Harri; Tolvanen, Asko; Lappalainen, Raimo
Low-intensity interventions for people suffering from depressive symptoms are highly desirable. The aim of the present study was to investigate the outcomes of a web-based acceptance and commitment therapy (ACT)–based intervention without face-to-face contact for people suffering from depressive symptoms. Participants ( N = 39) with depressive symptoms were randomly assigned to an Internet-delivered acceptance and commitment therapy (iACT) intervention or a waiting list control condition (WLC). Participants were evaluated with standardized self-reporting measures (Beck Depression Inventory [BDI-II], Symptom Checklist–90 [SCL-90], Acceptance and Action Questionnaire [AAQ-2], Five Facet Mindfulness Questionnaire [FFMQ], Automatic Thoughts Questionnaire [ATQ], and White Bear Suppression Inventory [WBSI]) at pre- and post-measurement. Long-term effects in the iACT group were examined using a 12-month follow-up. The iACT program comprised home assignments, online feedback given by master's-level students of psychology over a 7-week intervention period, and automated email-based reminders. Significant effects were observed in favor of the iACT group on depression symptomatology (between effect sizes [ESs] at post-treatment, iACT/WLC, g = .83), psychological and physiological symptoms (g = .60), psychological flexibility (g = .67), mindfulness skills (g = .53), and frequency of automatic thoughts (g = .57) as well as thought suppression (g = .53). The treatment effects in the iACT group were maintained over the 12-month follow-up period (within-iACT ES: BDI-II, g = 1.33; SCL-90, g = 1.04; ATQF/B [Frequency/Believability], FFMQ, WBSI, AAQ-II, g = .74-1.08). The iACT participants stated that they would be happy to recommend the same intervention to others with depressive symptoms. We conclude that an ACT-based guided Internet-delivered treatment with minimal contact can be effective for people with depressive symptoms.